2007
DOI: 10.1017/s0043933907001316
|View full text |Cite
|
Sign up to set email alerts
|

Sex identification in avian species using DNA typing methods

Abstract: Many avian species are considered sexually monomorphic. In monomorphic bird species, especially in young birds, sex is difficult to identify based on an analysis of their external morphology. For nestlings, sex identification is usually impossible by morphological examination. Sex identification in avian species is one of the key points of avian breeding and evolutionary studies. Through the knowledge of sex identification genes, poultry breeding programmes can be applied more successfully. Vent sexing, laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 37 publications
1
47
0
2
Order By: Relevance
“…The response differed also according to their gender. Reports in the literature indicate differentiation in acoustic signals of vocalizations between males and females (CERIT & AVANUS, 2007;GEBERZAHN et al, 2009), while other authors highlight that vocalization different responses may be an indicator of lack of welfare, i.e., stress (BRUMM et al, 2009;KOKOLAKIS et al, 2010;BAKER et al, 2012), corroborating the results of this study. We also observed that there was a difference between wave shapes and vocalization frequency of male broilers depending on genetic strain, what indicates that vocalization during welfare conditions was also different from that response obtained during thermal stress exposure.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The response differed also according to their gender. Reports in the literature indicate differentiation in acoustic signals of vocalizations between males and females (CERIT & AVANUS, 2007;GEBERZAHN et al, 2009), while other authors highlight that vocalization different responses may be an indicator of lack of welfare, i.e., stress (BRUMM et al, 2009;KOKOLAKIS et al, 2010;BAKER et al, 2012), corroborating the results of this study. We also observed that there was a difference between wave shapes and vocalization frequency of male broilers depending on genetic strain, what indicates that vocalization during welfare conditions was also different from that response obtained during thermal stress exposure.…”
Section: Resultssupporting
confidence: 90%
“…Audible warning signals are not produced by reflection, but when individuals are exposed to stress (MENDL et al, 2009;KOKOLAKIS et al, 2010). Another important aspect is that male and female birds perceive risk differently from each other (CERIT & AVANUS, 2007;VOLODIN et al, 2009); therefore, the response to lack of welfare, such as imminent risk factors, may be different for each gender. …”
Section: Ifmentioning
confidence: 99%
“…Discrimination of sex in poultry is done using different methods such as examining of feet, neck, feather colour and length as well as cloaca control, radiographic examination, footprint and hormonal or operational methods (Cerit and Avanus, 2007).Besides its importance for behavioural studies and wildlife management (Henry et al, 2015;Volodin et al, 2015), determination of sex is crucial for the profitability of agribusinesses. Zoometric measurement as a tool in sex discrimination has been examined in, for instance, mockingbirds (Fuchs and Montalti, 2016), owls (Tornberg et al, 2016), coots (Minias, 2015), Muscovy ducks (Oguntunji and Ayorinde, 2014) showing rather inconclusive results concerning predictability in terms of species and measurements traits.…”
Section: Introductionmentioning
confidence: 99%
“…Sex identification in Blackfaced Spoonbill amplified CHD-W and CHD-Z genes, with products of 658 and 464 base pair respectively [42], while sex determination in Cockatoo (parrot) species (Nymphicus hollandicus) from feather also possible [2].…”
Section: Chd Genes In Aviansmentioning
confidence: 99%
“…The feathers can be used as source of genomic DNA. DNA extraction from feathers is friendly to birds as it reduces handling stress, blood loss and chance of infection in them [2]. The constitution of sex chromosomes of birds is ZW for females and ZZ for males.…”
Section: Introductionmentioning
confidence: 99%